Role of dislocations in formation of ohmic contacts to heavily doped n-Si - Belyaev, A.E.; Pilipenko, V.A.; Anischik, V.M.; Petlitskaya, T.V.; Klad’ko, V.P.; Konakova, R.V.; Boltovets, N.S.; Korostinskaya, T.V.; Kapitanchuk, L.M.; Kudryk, Ya.Ya.; Vinogradov, A.O.; Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We present experimental results concerning a high density of structural defects
(in particular, dislocations) in the near-contact region of heavily doped n-silicon. They
appear in the course of firing Au Pd Ti Pd -Si n ohmic contact at 450С for
10 min in a vacuum of ~10 Pa⁻⁴ . These defects lead to appearance of metal shunts that
determine the current flow mechanism in these ohmic contacts. The calculated and
experimental temperature dependences of contact resistivity, ρс(Т), are in good
agreement. It is shown that ρс increases with temperature. This is characteristic of a
model of ohmic contacts with a high dislocation density in the near-contact region of
semiconductor